City beautiful post colonial analysis of the Arellano Plan of Iloilo City. - Salomon, Elgin Glenn R.
Postcolonialism describes the legacies of colonial power as it inscribes itself into the space of ?Others?. Postcolonial Otherness examines extremes asymmetries of power through imbalances of privilege, affluence and possession between the colonizers and colonized. At the same time, the colonizers can justify their conquest to establish systems of administration and instruction in their advantage. In the same manner, postcolonialism is considered to be a counter-discourse since it opposes Western hegemony like applying civilizing techniques by the colonizers. But the problem is that, these civilizing missions were not thoroughly questioned especially outside of the academe. One of the under-examined aspects of colonialism is urban planning. Urban planning function does not merely determine the use of space and design of the urban environment but also plays a huge role in how power is exercised. Taking from the framework of Siddharta Sen (2011) and David Brody (2010) which argues this thesis examines the blueprints of Juan Arellano?s (a pensionado) urban planning design, ?City Beautiful?, and engages this with existing urban plans in both the United States and the Philippines from the decades. It argues that such designs were premised by American colonial objectives domination, subjugation and control to reform Hispanized Filipinos into an Americanized one.